Unraveling the mystery: How autophagy deficiency in dopaminergic neurons drives human Parkinson’s disease - Sachiko Noda; Nobutaka Hattori (Molecular Brain)
Abstract Alpha-synuclein (α-synuclein), a key component of Lewy body pathology, is a classical hallmark of Parkinson’s disease. In previous studies, our group has examined dopaminergic neuron-specific Atg7 autophagy-deficient mice, observing α-synuclein aggregation in vivo. This pathological process led to dopamine neuron loss and age-related motor impairments. Further, in a recent study, we developed a new mouse model by crossing human α-synuclein bacterial artificial chromosome transgenic mice with dopaminergic neuron-specific Atg7 conditional knockout mice to further investigate these mechanisms. These model mice exhibited accelerated Lewy body-like pathology and motor dysfunction, providing additional evidence that autophagy deficiency exacerbates synuclein toxicity in vivo. This nano-review provides essential clues that autophagy deficiency in dopamine neurons may contribute to the onset of human synuclein diseases.